Espalhamento Raman na risperidona em condições extremas de temperatura - Gomes, Wagner Pereira (2022)
In this work, the medicine risperidone (C23H27FN4O2) was analyzed using Raman spectroscopy techniques under extreme temperature conditions, in order to investigate its vibrational properties. Risperidone is a medicine classified as an atypical antipsychotic, used in the treatment of schizophrenia, autism in children and adolescents and bipolar disorder. The study of medicine properties and their changes caused by thermodynamic variations has been gaining great importance in the pharmaceutical industry, since the changes affect the quality and functioning of these medicines. Therefore, this analysis was carried out in order to understand the behavior of crystal structure of risperidone under a wide temperature variation. DSC (Differential Scanning Calorimetry) thermal analysis experiments were performed in the range between 133 K and 653 K (-140 °C and 380 °C) and Raman spectroscopy at low temperatures, up to 12 K (-261 °C) and at high temperatures, up to 393 K (120 C). The DSC experiment showed that risperidone does not show any phase transition at low temperatures while at high temperatures the DSC experiment shows an endothermic peak at 173 °C, related to melting point and two exothermic peaks, at 210 °C and 250 °C, possibly associated with the decomposition of the sample. The results of the low temperature and high temperature Raman spectroscopy experiments of risperidone showed little change in the Raman spectra, with no indication that the material undergoes any phase transition. Therefore, the medicine risperidone with monoclinic structure remains stable over the entire temperature range between 12 K and 393 K.